Superior high-rate lithium-ion storage on Ti2Nb10O29 arrays via synergistic TiC/C skeleton and N-doped carbon shell. (December 2018) - Yao, Zhujun; Xia, Xinhui; Zhang, Yan; Xie, Dong; Ai, Changzhi; Lin, Shiwei; Wang, Yadong; Deng, Shengjue; Shen, Shenghui; Wang, Xiuli; Yu, Yan; Tu, Jiangping
Abstract: Directional construction of high-rate anode is of great importance for the development of next-generation large-power lithium ion batteries. In the present work, we report a powerful combined strategy for smart construction of omnibearing conductive networks composed of TiC/C arrays core and N-doped carbon (NC) shell to sandwich Ti2 Nb10 O29 (TNO) nanoparticles forming integrated NC-TNO@TiC/C core/shell arrays. Except for good electronic conductivity and high rigidity from TiC/C arrays skeleton, lower energy barrier of Li ion is obtained via the N-doped carbon layer facilitating the ion/electron transport kinetics according to DFT results. Accordingly, the NC-TNO@TiC/C electrode shows preeminent high-rate capacities (318 mA h g −1 at 1 C and 202 mA h g −1 at 50 C) and a long cycle life with a capacity retention of 85% after 10, 000 cycles at 10 C, better than other TNO counterpart due to the positive synergistic effect on enhanced ion/electron transfer and reinforced structure from conductive NC outer layer and TiC/C skeleton. The full cell assembled by NC-TNO@TiC/C anode and LiFePO4 (LFP) cathode also shows excellent electrochemical properties with promising application prospect. This polybasic structure design could offer guidelines for fabrication of other hybrid high-rate electrodes for energy storage devices. Highlights: TNO nanoparticles are sandwiched by TiC/C core and N-doped carbon shell. The NC-TNO@TiC/C electrode shows preeminent high-rate capacities. Low energy barrier of Li ion is achieved in NC layer according to DFT result. TiC/C core and N-doped carbon shell provide fast transfer path of electron.